A companion to Heidegger's Phenomenology of religious life - McGrath, S. J., 1966-; Wierciński, Andrzej (Elementa (Rodopi (Firm)), 2010)
In the academic year 1920-1921 at the University of Freiburg, Martin Heidegger gave a series of lectures on the phenomenological significance of the religious thought of St. Paul and St. Augustine. The publication of these lectures in 1995 settled a long.